The Rise of the Mutants: Obtaining Regulatory Approval for the Release of Genetically Modified Mosquitoes - Aldrich, Joel F. (Science and Technology Law Review, 2016)
Over the last few decades, sterile insect technique has emerged as an attractive means of controlling insect populations. Recently, scientists have considered releasing genetically modified mosquitoes into the Florida Keys as a means of controlling the spread of certain exotic, insect-borne viruses. Although transgenic insects have previously been tested in the field, these organisms have traditionally been regulated under the authority of APHIS. The present technology, however, is pending approval as a “new animal drug” under the FDA. This Article seeks to shed light on this inconsistency by examining the legal framework surrounding the regulation of transgenic insects and discussing other instructive examples of transgenic animal regulation. Additionally, this Article examines the definition of “new animal drug” under the FDA and analyzes how the genetically modified mosquitoes might fall under that designation more appropriately than a product designation under the EPA or APHIS. This Article concludes by addressing some of the issues with the current biotech regulatory environment and proposing improvements to add clarity to a given transgenic insect’s product designation.